Estrés laboral y resiliencia durante la pandemia COVID-19 en trabajadores de la empresa privada Transporte Júpiter S.R.L. Iquitos 2021 - Vergara Huayabán, Maria Teresa (2023)
The objective of the research was to determine the relationship between work stress and resilience during the COVID-19 pandemic in workers of the private company Transporte Júpiter, Iquitos 2021. Methodology: the research was quantitative, non-experimental design, correlational and transversal; The population consisted of 100 workers, the sample size was 100 workers. The data collection technique was the survey and the instruments were two: the Work Stress Scale (0.95% validity and 66.90% reliability) and the Resilience Scale (87% validity and 87% reliability). The results when applying the non-parametric statistical test Spearman's Rho, show a correlation between low-level work stress and high-level resilience, with a significance p=0.011 and negative with a coefficient -,253. The study concludes that there is a significant and negative correlation between work stress and resilience during the COVID-19 pandemic in workers of the private company Transporte Júpiter, Iquitos 2021.